Understanding the gum dichromate process in pictorialist photographs: A literature review and technical study. (1st July 2013) - Vila, Anna; Centeno, Silvia A.; Barro, Lisa; Kennedy, Nora W.
Abstract : In the late 1800s, pictorialist photographers favored a diversity of photographic techniques, including the gum dichromate process. Sometimes superimposed over other photographic images such as platinum and silver prints, the gum dichromate process utilizes a light-sensitive mixture of gum arabic, pigment, and a potassium dichromate solution hand-applied onto a sheet of paper and exposed to light while in direct contact with a negative. The definitive identification of this process has proven to be a challenge due to many variations and intermingling of techniques used by photographers of this period. This research began with a search through the historic literature, followed by the creation of test samples based on historic recipes, and the X-ray fluorescence analysis of these tests. The identification of pigments and the presence of chromium have been associated with the gum dichromate or other dichromated colloid processes in the past. Research results reveal that the presence of chromium may have more complex sources, requiring a more discriminating approach and a modified protocol for the identification of gum dichromate photographs.